2012
DOI: 10.3233/jad-2011-111268
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Less Common and “Disregarded” Neurodegenerative Pathologies on Dementia Burden in a Population-Based Cohort

Abstract: Epidemiological studies investigating the pathological bases of late onset dementia focus on classical markers such as plaques and tangles. The significance of pathologies characteristically associated with rare dementia syndromes such as Pick bodies and severe neuronal loss are considered to be well defined. The significance of other pathologies, often accepted as a feature of neurodegenerative syndromes, such as Hirano bodies and gliosis is not clear. This study investigated the significance of these rarer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…By using a NPC score and analyzing it against CDR-SOB, IQCODE, and NPI, we showed that neuropathological comorbidity is related to increased risk of dementia and the severity of neuropsychological symptoms. These results are in line with other cohorts from HICs [9,10,19,20,83]. One open question refers to whether neuropathological comorbidity results in a synergistic effect of worsening cognition in humans, as has been shown in animal models [55].…”
Section: Discussionsupporting
confidence: 88%
“…By using a NPC score and analyzing it against CDR-SOB, IQCODE, and NPI, we showed that neuropathological comorbidity is related to increased risk of dementia and the severity of neuropsychological symptoms. These results are in line with other cohorts from HICs [9,10,19,20,83]. One open question refers to whether neuropathological comorbidity results in a synergistic effect of worsening cognition in humans, as has been shown in animal models [55].…”
Section: Discussionsupporting
confidence: 88%
“…Amygdala predominant disease may reflect an alternate progression of LB pathology. Whilst it is commonly proposed that neocortical and limbic Lewy body pathology are central in determining cognitive impairment and dementia [115,120], others have challenged this to suggest Lewy body pathology in the brainstem may also be important correlates of cognitive impairment [65]; however this finding is not replicated in all studies [115]. Some propose the importance of AD pathology burden, and suggest neocortical Lewy body pathology is not sufficient to cause severe global cognitive impairment and that AD pathology must be present, reflecting a synergistic relationship [92].…”
Section: Mixed Lewy Body and Ad Pathologiesmentioning
confidence: 99%
“…The distribution of TDP-43 pathology varies remarkably (range 13 to 46%), partly due to the fact that different antibodies are used and also due to how the presence of TDP-43 immunoreactivity is specified [ 35 ]. Furthermore, less common NDDs – such as multiple system atrophy, PSP, corticobasal degeneration, tangle-predominant dementia, FTLD-TDP [ 72 ] and even Pick bodies – are also reported in a subset of their subjects (usually below 5 to 10%) [ 5 , 27 , 36 , 41 , 45 , 51 ]. Application of phospho-tau immunostaining in several anatomical regions allowed the VITA study to identify a spectrum of further tau pathologies associated with the aging brain, including their association with cognitive decline [ 5 , 6 ].…”
Section: Frequency Of Neurodegenerative Conditions In the Aging Brainmentioning
confidence: 99%